Gender Studies in the State and Constitution (Implementation of Law Enforcement in Indonesia) - Aflah Husnaini Matondang; Hilda Melani Purba; Irlyanova Sabina; Nadia Syahfitri (Journal of Contemporary Gender and Child Studies, 2022)
The implementation of law enforcement in Indonesia is still relatively weak, so a deeper analysis of the causes of the occurrence is needed. This study aims to examine gender in the state and law, a study of the implementation of law enforcement in Indonesia. This study uses a qualitative approach with descriptive analytical study method. Data collection is based on in-depth interviews, participant observation and documentation studies. Furthermore, the data were analyzed using data reduction techniques, presenting data to drawing conclusions. The results of this study conclude that law enforcement in Indonesia is still weak, the integration of law enforcement officers is not well established, the level of performance implementation by law enforcement officers is low, and the application of law is blunt up and down (non-Pancasilais).